2023
DOI: 10.1177/08944393231178603
|View full text |Cite
|
Sign up to set email alerts
|

Like, Comment, and Share on TikTok: Exploring the Effect of Sentiment and Second-Person View on the User Engagement with TikTok News Videos

Abstract: TikTok—the world’s most downloaded app since 2020, has become a place for more than silly dancing and lip-syncing. TikTok users are increasingly turning to TikTok for news content. Meanwhile, news publishers are embracing TikTok to reach a younger audience. We aim to examine the content strategy adopted by the most-followed news publishers on TikTok and how effective their TikTok strategy is in spurring audience engagement in terms of liking, commenting, and sharing. This study retrieved 101,292 TikTok news vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 67 publications
0
6
0
Order By: Relevance
“…Relevant studies have also confirmed such patterns for other platforms (e.g., Ledwich & Zaitsev, 2020). For example, TikTok's user algorithm similarly promotes content from conspiracy groups-QAnon, Three Percenters, and Oath Keepers (Albertazzi & Bonansinga, 2023;Cheng & Li, 2023).…”
mentioning
confidence: 76%
See 1 more Smart Citation
“…Relevant studies have also confirmed such patterns for other platforms (e.g., Ledwich & Zaitsev, 2020). For example, TikTok's user algorithm similarly promotes content from conspiracy groups-QAnon, Three Percenters, and Oath Keepers (Albertazzi & Bonansinga, 2023;Cheng & Li, 2023).…”
mentioning
confidence: 76%
“…The TikTok algorithm bases recommendations on a user's interactions with content on the app (Cheng & Li, 2023). The For You Page (FYP) shows users personalized content curated specifically for them by the TikTok algorithm.…”
mentioning
confidence: 99%
“…These videos will be carefully analyzed to understand the context, content, and messages conveyed by UNP KKN students. Additionally, interviews were conducted with relevant respondents, such as students involved in creating video content, local residents, and stakeholders such as supervising lecturers and university authorities (Cheng & Li, 2023). These interviews aim to gather perceptions and views on the incident and to understand its impacts on the various parties involved (McCashin & Murphy, 2023).…”
Section: Methodsmentioning
confidence: 99%
“…Fractures, namely holes that form in the dam body when it collapses, occur before the dam completely collapses [7]. This happened before the dam actually collapsed [8]. Understanding of failure mechanisms is still lacking, regardless of whether the dam in question is a concrete dam or an earthfill dam.…”
Section: Literature Reviewmentioning
confidence: 99%